Effects of delta9-tetrahydrocannabinol on the rates of oxygen consumption of mice. - Pertwee, R G (1977)
1. Experiments with untreated mice confirmed that at ambient temperatures below 30 degrees C, the oxygen consumption rate of mice normally kept at about 23 degrees C varies inversely with ambient temperature. 2. At given ambient temperatures in the range 20 to 31 degrees C the oxygen consumption rate was 32 to 43% greater for restrained than for unrestrained mice. 3. Hypothermia induced in restrained mice by delta9-tetrahydrocannabinol (delta9-THC) (1.0 to 4.0 mg/kg i.v.) was accompanied by marked falls in the rate of oxygen consumption. The size of these falls parallelled the degree of hypothermia and increased both with increases in dose and with decreases in the ambient temperature. The oxygen consumption rates of unrestrained mice were also lowered by hypothermic doses (10 to 40 mg/kg i.p.) of delta9-THC. 4. The maximum falls in oxygen consumption rate occurred at earlier times after drug administration than the maximum falls in rectal temperature. 5. At none of the ambient temperatures studied did the oxygen consumption rates of delta9-THC-treated mice fall significantly below the basal levels (59 +/- 3 ml 25 g-1 h-1) of unrestrained, resting mice at 30 degrees C. 6. The hypothesis that reduced rates of heat production contribute significantly towards the hypothermia induced by delta9-THC in our experiments is discussed. The possibility that biological processes responsible for increased heat production in response to cold are more sensitive to delta9-THC than those processes governing basal rates of heat production at thermally neutral environmental temperature is also raised.